Understanding Lifestyle Marketing Mix (LISA) Impacts On Brand Equity And Customer Equity In Beauty Services Industries: Evidence From Jakarta, Indonesia - Bernard T. Widjaja; Hery Winoto Tj (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines how lifestyle-oriented marketing complements the traditional service marketing mix in shaping brand equity and customer equity in high-involvement service contexts. It investigates the relative and combined effects of the service marketing mix (SERV) and lifestyle marketing mix (LIST) on brand equity and customer equity in Jakarta's premium beauty services industry. Using Structural Equation Modeling (SEM) with survey data from 200 premium salon customers, results show that both SERV and LIST significantly and positively affect brand equity, with lifestyle elements demonstrating stronger influence than traditional service components. Brand equity fully mediates the relationship between the integrated SERVLIST mix and customer equity. The study reconceptualizes lifestyle as an operable marketing mix component, demonstrating that brand equity formation in lifestyle-driven service settings depends more on lifestyle congruence than service performance alone. Businesses are recommended to integrate lifestyle-oriented strategies alongside traditional service quality measures to maximize brand equity and customer loyalty.